Volume 5: Heat Transfer, Parts a and B 2011
DOI: 10.1115/gt2011-46402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Leakage Loss and Heat Transfer in a Straight Through Labyrinth Seal

Abstract: Labyrinth seals are extensively used in turbomachinery to prevent high pressure gas from flowing into a region of low pressure. Because of thermal expansions and centrifugal forces, the actual seal clearance can vary based on engine conditions. Pressure ratio, Reynolds number, tip geometry, and seal clearance all affected the sealing performance. This paper deals with its influence on the leakage flow and heat transfer coefficient through a thirteen teeth straight through labyrinth seal. Three gaps were experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 0 publications
3
17
1
Order By: Relevance
“…With the experimental data, a simple correction equation, which correlates Nu with Re, pitch width, and gap width, was proposed in their study. Recently, Micio et al, [10] experimentally investigated the leakage and heat transfer performance in the straight-through labyrinth seal with 13 fins. They found that their numerical results agree well with the test data with respect to the Nu distributions on seal stator surface while Nu on the rotor surface is overpredicted significantly.…”
Section: Fig 1 Photos Of Labyrinth Fin Damages In Realistic Operationsmentioning
confidence: 99%
See 4 more Smart Citations
“…With the experimental data, a simple correction equation, which correlates Nu with Re, pitch width, and gap width, was proposed in their study. Recently, Micio et al, [10] experimentally investigated the leakage and heat transfer performance in the straight-through labyrinth seal with 13 fins. They found that their numerical results agree well with the test data with respect to the Nu distributions on seal stator surface while Nu on the rotor surface is overpredicted significantly.…”
Section: Fig 1 Photos Of Labyrinth Fin Damages In Realistic Operationsmentioning
confidence: 99%
“…Recently, Micio et al, [10] experimentally investigated the leakage and heat transfer performance in the straight-through labyrinth seal with 13 fins. By using the low-Re k-(ú turbulence model, the effects of sealing clearance, step position, and step height on the flow pattem and heat transfer coefficient distributions were investigated based on the experimental work of Willenborg et al,[9] [10] to investigate the heat transfer and windage heating effect in the rotational labyrinth seals with smooth and honeycomb lands. The local Nu distributions on both rotor and stator surfaces were measured at four different Reynolds numbers.…”
Section: Fig 1 Photos Of Labyrinth Fin Damages In Realistic Operationsmentioning
confidence: 99%
See 3 more Smart Citations